Microstructural investigation of shear localization in the Ersfjord granite, Kvaløya, Troms: A case study of kinematics, deformation mechanisms and fabric relationships - Persen, Daniel (UiT Norges arktiske universitet, 2014)
The present “case study” deals with Paleozoic-Mesozoic oblique-dextral strike-slip shear zones situated within the Ersfjord granite (1,79 Ga), that are believed to give valuable insight into fault- and fluid flow mechanics from the brittle-ductile transition zone. Mesoscopic observations combined with microstructural evidence and geochronology suggests that Late Carbonifereous-Early Triassic fault activity took place, associated with the evolution of the continental margin of Northern Norway. Initial fault movement at minimum pressure-temperature conditions of c. 350°C and c. 290 MPa (c. 11-12 km depth) caused cataclastic failure. The faults appear as single or adjacent connected zones where the cataclasites reactivated the earlier ductile fabric, although most of the rock has also undergone some strain. Three deformation phases were identified: (1) Svecofennian deformation that produced gneiss foliation throughout the granite; (2) formation of semiductile shear zones along- and at a low angle to the foliation fabric; (3) a post-ductile brittle event which propagated along the pre-existing weak fabric and caused overprinting. The studied heterogeneities have acted as fluid canals, where microstructures suggest that pore pressure locally reached lithostatic levels (290 MPa). The fracturing of feldspar phorphyroclasts within the mylonites, the grain size reduction, the deformation mechanisms and the mineral assemblages all point towards greenschist facies conditions during shearing. Grain size reduction caused a switch from dislocation creep to diffusion creep deformation mechanisms. The occurrence of pumpellyite during late stage faulting implies minimum pressure and temperature conditions of c. 275°C and c. 220 MPa (c. 8-9 km depth). The absence of post-kinematic grain growth supports an exhumation history dominated by erosional processes.